Eye Movement in Unipolar and Bipolar Depression: A Systematic Review of the Literature - Carvalho, Nicolas; Laurent, Eric; Noiret, Nicolas; Chopard, Gilles; Haffen, Emmanuel; Bennabi, Djamila; Vandel, Pierre (Frontiers in Psychology, 2015)
Background: The analysis of eye movements (EM) by eye-tracking has been carried out for several decades to investigate mood regulation, emotional information processing, and psychomotor disturbances in depressive disorders. Method: A systematic review of all English language PubMed articles using the terms “saccadic eye movements” OR “eye-tracking” AND “depression” OR “bipolar disorders” was conducted using PRISMA guidelines. The aim of this review was to identify the specific alterations of EM in unipolar and bipolar disorders. Results: Unipolar depression has been characterized by an increase in reaction time in prosaccade and antisaccade tasks, and a specific attraction for negative pictures. Bipolar disorders have been associated with an increase in reaction time in prosaccade and antisaccade tasks, and an attraction for threatening images. Methodological limitations include mixed samples sometimes undifferentiating unipolar and bipolar patients, or an absence of specification regarding the polarity of the episode in bipolar disorders. Moreover, we found no study explicitly comparing EM in both unipolar depression and bipolar disorders. Conclusion: Unipolar depression and bipolar disorders can be characterized by different psychomotor alterations and affective regulation strategies. Eye movement analysis could be a useful tool as a potential biomarker to distinguish between the two diseases. However, further research is needed to directly and systematically compare eye movement data in both diseases under strictly identical experimental conditions.